FOREWORD, Pendhapa: Vol. XI, No. 2. - sumarno, sumarno (Pendhapa, 2020)
History is the circumstances and events of human life in the past including previous achievements that are disclosed again. The glory, advancement, and fame of a certain nation, state, tribe or community group are often retold to educate, remember, and generate a positive spirit to build the future through various ways with various points of view in accordance with their respective fields of knowledge and passion.Jaza Chehata Hadi, in designing the interior of the Port, seeks to bring back the old Semarang atmosphere with the concept of Venice van Java, the nickname of Semarang city – Central Java Indonesia, years ago, due to many rivers in the middle of the city just like the city of Venice (Italy). The icons, documentation and knick-knacks of the past are presented to bring out the old Semarang atmosphere.The second article is Mahdi Nurcahyo's article, revealing how people with visual impairment or blindness recognize and present some aspects of convenience in the house where he lives in, as a part of giving meaning to everyday life through his sense of experience and sensitivity to arrange space according to his body's comfort. The third article by Muhammad Fadilah Fatah and his friends concerns on the design of a chair as a sitting facility which combines functions of bag, charger, as well as table by utilizing waste as its raw material to reduce environmental pollution.The existence of batik for Indonesian people is as the nation's ancestral cultural heritage. Batik covers various aspects such like philosophy, techniques or production, community economy, batik motifs, coloring, identity and other aspects. In the Edition XI, No. 2 of Pendhapa: Journal of Interior Design, Art and Culture, there are three articles related to batik. Two articles contain the results of some designs of the infrastructure facilities for the interiors to protect and develop batik. The revitalization of a noble's residence that had been neglected into a batik shop and museum in Laweyan village, Surakarta, Central Java, Indonesia, is the article of Yosafat Adi Pradipta and Raden Ersnathan Budi Prasetyo. Another article about batik is the interior design of Omah Batik in Bayat, Klaten, Central Java, Indonesia as a means of protecting and developing batik, by Annisa Isma Safitri and Joko Budiwiyanto. The last article is batik motifs as a design idea for hotel design, written by Wahyu Tri Widiyanto and Putri Sekar Hapsari.History stores a lot of knowledge, philosophy, science, wisdom, and many other things. The time span of batik work that has been going on for generations has become a part of the history of the cultural journey of the people, especially in Java. The preservation and development is a shared responsibility. The scholars, the researchers, and the academics morally have the obligation to always be sensitive to various things, especially related to phenomena in their surrounding environment.